ALLERGIC FUNGAL SINUSITIS IN CHILDREN: REVIEW - Lutfullaev Umrillo Lutfullaevich; Kobilova Shakhodat Shokirovna; Madaminova Nigora Ergashevna; Tukhtaev Abror Axtamovich; Muzrapov Turgun Bobokulovich (Web of Journals Publishing, 2025)
A subtype of eosinophilic chronic rhinosinusitis (CRS), allergic fungal sinusitis (AFS) is distinguished by type I hypersensitivity, nasal polyposis, eosinophilic mucus, characteristic computed tomography scan findings, and the presence of fungus on surgical specimens without tissue invasion. Given the relatively early age of onset and the challenge of controlling AFS with commercially available treatment regimens, this refractory subtype of CRS is of particular relevance to the pediatric community. AFS diagnosis almost always necessitates surgical surgery. One of the cornerstones of the pediatric AFS treatment paradigm is postoperative adjuvant medicinal therapy.
Keywords: Pediatric sinusitis, Pediatric rhinosinusitis, Allergic fungal sinusitis, Management of rhinosinusitis, Chronic rhinosinusitis.